2011
DOI: 10.1017/s0014479711000901
|View full text |Cite
|
Sign up to set email alerts
|

THE WATER RELATIONS OF RUBBER (HEVEA BRASILIENSIS): A REVIEW

Abstract: SUMMARYThe results of research done on water relations of rubber are collated and summarised in an attempt to link fundamental studies on crop physiology to crop management practices. Background information is given on the centres of origin (Amazon Basin) and production of rubber (humid tropics; south-east Asia), but the crop is now being grown in drier regions. The effects of water stress on the development processes of the crop are summarised, followed by reviews of its water relations, water requirements an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 45 publications
1
32
0
2
Order By: Relevance
“…Our study, however, does not support this observation: the top layer of rubber plantation soils was wetter compared with natural forest soils. The transpiration rates of rubber trees growing under tropical humid or monsoon climates are actually not very high (<3 mm day −1 ; Carr, 2011;Kobayashi et al, 2014;Niu, Röll, Meijide, Hendrayanto, & Hölscher, 2017). To explain the difference in soil water usage between natural forest and rubber plantation, further studies need to cover both land uses and all components of the water cycle.…”
Section: Soil Moisture Content As a Decisive Driver For The Ch 4 Flmentioning
confidence: 99%
“…Our study, however, does not support this observation: the top layer of rubber plantation soils was wetter compared with natural forest soils. The transpiration rates of rubber trees growing under tropical humid or monsoon climates are actually not very high (<3 mm day −1 ; Carr, 2011;Kobayashi et al, 2014;Niu, Röll, Meijide, Hendrayanto, & Hölscher, 2017). To explain the difference in soil water usage between natural forest and rubber plantation, further studies need to cover both land uses and all components of the water cycle.…”
Section: Soil Moisture Content As a Decisive Driver For The Ch 4 Flmentioning
confidence: 99%
“…8). SON, 2010, SON, 2011and DJF, 2011-2012 at CRRI because of their original narrow range of D. The theoretical ratio 0.60 (Oren et al, 1999) is shown by a solid line for each site. -Claramonte et al (2008) surmised that the introduction of rubber plantations may reduce stream flow leading to drier conditions throughout a catchment area, mainly because of high water use by rubber trees at the very peak of the dry season (cf., Fox et al, 2014).…”
Section: Analyses Of Stomatal Conductancementioning
confidence: 99%
“…On the other hand, some studies reported that rubber plantations replacing non-forested lands could act as a carbon sinks (Wauters et al, 2008). Further, while eddy covariance measurements in rubber revealed high plantation water use and a large proportion of energy being used to drive evapotranspiration for most of the year (Tan et al, 2011;Giambelluca et al, submitted for publication, hereinafter referred to as submitted manuscript, 2015), the results of sapflow measurements of individual rubber trees showed water use of rubber plantations may not be as high as anticipated (Isarangkool Na Ayutthaya et al, 2011;Carr, 2012;Kobayashi et al, 2014), but these findings might be related to differences in regional climate, geography, physiological adaptations, and measurement method. Of concern to our research, large-scale land use changes to rubber plantations may have important implications for local-to-regional carbon and water balances, but they still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid conversion of tropical forests to agriculture, timber production or other uses has generated vast, human-dominated landscapes with negative consequences for tropical forest ecosystems (Gardner et al, 2009; Gibson et al, 2011). Rubber tree ( Hevea brasiliensis ) is an evergreen tree species in the rainforests of Amazon (Carr, 2012; Chen and Cao, 2015) and introduced to tropical Asia at the end of 19th century (Limkaisang et al, 2005). Global rubber plantations reached 10.06 million ha in 2010 (FAO, 2010) with 81% in South and Southeastern Asia (FAO, 2010).…”
Section: Introductionmentioning
confidence: 99%